The impacts of buildability factors on formwork labour productivity of columns - M. Jarkas, Abdulaziz (Journal of Civil Engineering and Management, 2010)
The impacts of buildability on formwork labour productivity of major in situ reinforced concrete elements such as, foundations, walls, columns, beams and slabs, are yet to be determined and quantified. The labour unit cost of columns formwork, in comparison with other constituents of the reinforced concrete frame, is constantly higher due to the forming complexity of these elements, especially non‐rectangular shapes, and the small output achieved in the operation. Therefore, the objective of this research is to investigate the impacts of buildability factors on columns formwork labour productivity. To achieve this objective, a large volume of productivity data was collected and analyzed using the categorical‐regression method. As a result, the impacts of the grid patterns, variability of column sizes, repetition, total and aver‐age shutter size, and geometry of columns are quantified. Apart from the variability of column sizes, the findings show significant effects of these factors on labour productivity, which can be used to provide designers feedback on how well their designs consider the requirements of buildability principles, and the consequences of their decisions on labour efficiency. Moreover, the depicted patterns of results may provide guidance to construction managers for effective activity planning and efficient labour utilization.First Published Online: 10 Feb 2011